Hadith #1479 - Muwatta Malik (Muwatta Malik)
Yahya related to me from Malik from Hisham ibn Urwa from his father from Zaynab bint Abi Salama from Umm Salama, the wife of the Prophet, may Allah bless him and grant him peace, that the Messenger of Allah, may Allah bless him and grant him peace, said, âI am but a man to whom you bring your disputes. Perhaps one of you is more eloquent in his proof than the other, so I give judgement according to what I have heard from him. Whatever I decide for him which is part of the right of his brother,
Grade:

Hadith #1480 - Muwatta Malik (Muwatta Malik)
Malik related to me from Yahya ibn Said from Said ibn al-Musayyab that Umar ibn al-Khattab had a dispute brought to him between a muslim and a jew. Umar saw that the right belonged to the jew and decided in his favour. The jew said to him, âBy Allah! You have judged correctly.â So Umar ibn al-Khattab struck him with a whip and said, âHow can you be sure.â The jew said to him, âWe find that there is no judge who judges correctly but that there is an angel on his right side and an angel
Grade:

Hadith #1481 - Muwatta Malik (Muwatta Malik)
Yahya related to me from Malik from Abdullah ibn Abi Bakr ibn Muhammad ibn Amr ibn Hazm from his father from Abdullah ibn Amr ibn Uthman from Abu Amra al-Ansari from Zayd ibn Khalid al-Juhani that the Messenger of Allah, may Allah bless him and grant him peace, said, âShall I not tell you who is the best of witnesses? The one who brings his testimony before he is asked for it, or tells his testimony before he is asked for it.â
Grade:

Hadith #1482 - Muwatta Malik (Muwatta Malik)
Malik related to me that Rabia ibn Abi Abd ar-Rahman said, âAn Iraqi man came before Umar ibn al-Khattab and said, âI have come to you because of a matter which has no beginning and no end.â Umar said, âWhat is it?â The man said, âFalse testimony has appeared in our land.â Umar said, âIs that so?â He said, âYes.â Umar said, âBy Allah! A man is not detained in Islam without just witnesses.â â
Grade:

Hadith #1483 - Muwatta Malik (Muwatta Malik)
Malik related to me that Umar ibn al-Khattab said, âThe testimony of some one known to bear a grudge or to be unreliable is not accepted.â
Grade:

Hadith #1484 - Muwatta Malik (Muwatta Malik)
Yahya said from Malik that he heard from Sulayman ibn Yasar and others that when they were asked whether the testimony of a man flogged for a hadd crime was permitted, they said, âYes, when repentance (tawba) appears from him.â Malik related to me that he heard Ibn Shihab being asked about that and he said the like of what Sulayman ibn Yasar said. Malik said, âThat is what is done in our community. It is by the word of Allah, the Blessed, the Exalted, âAnd those who accuse women who are
Grade:

Hadith #1485 - Muwatta Malik (Muwatta Malik)
Grade:

Hadith #1486 - Muwatta Malik (Muwatta Malik)
Yahya said, âMalik said from Jafar ibn Muhammad from his father that the Messenger of Allah, may Allah bless him and grant him peace, pronounced judgement on the basis of an oath with one witness.â
Grade:

Hadith #1487 - Muwatta Malik (Muwatta Malik)
From Malik from Abuâz-Zinad that Umar ibn Abd al-Aziz wrote to Abd al-Hamid ibn Abd ar-Rahman ibn Zayd ibn al-Khattab who was the governor of Kufa, âPronounce judgement on the basis of an oath with one witness.â
Grade:

Hadith #1488 - Muwatta Malik (Muwatta Malik)
Malik related to me that he heard that Abu Salama ibn Abd ar- Rahman and Sulayman ibn Yasar were both asked, âDoes one pronounce judgement on the basis of an oath with one witness?â They both said, âYes.â Malik said, âThe precedent of the sunna in judging by an oath with one witness is that if the plaintiff takes an oath with his witness, he is confirmed in his right. If he draws back and refuses to take an oath, the defendant is made to take an oath. If he takes an oath, the claim aga
Grade:

Hadith #1489 - Muwatta Malik (Muwatta Malik)
Yahya said that Malik spoke about a man who died and had a debt owing to him and there was one witness, and some people had a debt against him and they had only one witness, and his heirs refused to take an oath on their rights with their witness. He said, âThe creditors take an oath and take their rights. If there is anything left over, the heirs do not take any of it. That is because the oaths were offered to them before and they abandoned them, unless they say, âWe did not know that our c
Grade:

Hadith #1490 - Muwatta Malik (Muwatta Malik)
Yahya said, âMalik said about Jamil ibn Abd ar-Rahman al-Muadhdin that he was present with Umar ibn Abd al-Aziz when he was judging between people. If a man came to him with a claim against a man, he examined whether or not there were frequent transactions and dealings between them. If there were, the defendant could make an oath. If there was nothing of that nature he did not accept an oath from him.â Malik summed up, âWhat is done in our community is that if some one makes a claim agains
Grade:

Hadith #1491 - Muwatta Malik (Muwatta Malik)
Yahya said, âMalik said from Hisham ibn Urwa that Abdullah ibn az-Zubayr gave judgment based on the testimony of children concerning the injuries between them.â Malik said, âThe generally agreed on way of doing things in our community is that the testimony of children is permitted concerning injuries between them. It is not accepted about anything else. It is only permitted between them if they testify before they leave the scene of the incident and have been deceived or instructed. If the
Grade:

Hadith #1492 - Muwatta Malik (Muwatta Malik)
Yahya said, Malik related to us from Hisham ibn Hisham ibn Utba ibn Abi Waqqas from Abdullah ibn Nistas from Jabir ibn Abdullah al- Ansari that the Messenger of Allah, may Allah bless him and grant him peace, said, âIf someone swears a false oath near this mimbar of mine, he will take his seat in the fire.â â
Grade:

Hadith #1493 - Muwatta Malik (Muwatta Malik)
Malik related to me from al-Ala ibn Abd ar-Rahman from Mabad ibn Kab as-Salami from his brother Abdullah ibn Kab ibn Malik al-Ansari from Abu Umama that the Messenger of Allah, may Allah bless him and grant him peace, said, âWhoever cuts off the right of a muslim man by his oath, Allah forbids him the Garden and obliges the Fire for him.â They said, âEven if it is something insignificant, Messenger of Allah?â He said, âEven if it is a tooth-stick, even if it is a tooth- stick,â repea
Grade:

Hadith #1494 - Muwatta Malik (Muwatta Malik)
Yahya said that Malik had said from Daâud ibn al-Husayn that he heard Abu Ghatafan ibn Tarif al-Muriyi say, âZayd ibn Thabit al-Ansari and Ibn Muti had a dispute about a house which they shared. They went to Marwan ibn al-Hakam who was the Amir of Madina. Marwan decided that Zayd ibn Thabit must take an oath on the mimbar. Zayd ibn Thabit said, âI swear to it where I am.â Marwan said, âNo, by Allah! only in the place of sorting out claims (i.e. the mimbar).â Zayd ibn Thabit began to
Grade:

Hadith #1495 - Muwatta Malik (Muwatta Malik)
Yahya said, âMalik related to us from Ibn Shihab from Saâid ibn al-Musayyab that the Messenger of Allah, may Allah bless him and grant him peace, said, âThe pledge given as security is not forfeited.â â Malik said, âThe explanation of that according to what we think â and Allah knows best â is that a man gives a pledge to somebody in security for something. The pledge is superior to that for which he pawned it. The pledger says to the pawn-broker, âI will bring you your due, af
Grade:

Hadith #1496 - Muwatta Malik (Muwatta Malik)
Yahya said, âI heard Malik say that if a man pledges his garden for a stated period and the fruits of that garden are ready before the end of that period, the fruits are not included in the pledge with the real estate, unless it is stipulated by the pledger in his pledge. However, if a man receives a slave-girl as a pledge and she is pregnant or she becomes pregnant after his taking her as a pledge, her child is included with her. âA distinction is made between the fruit and the child of the
Grade:

Hadith #1497 - Muwatta Malik (Muwatta Malik)
Yahya said that he had heard Malik say, âThe undisputed way of doing things in our community concerning pledges is that in cases where land or a house or an animal are known to have been destroyed whilst in the possession of the broker of the pledge, and the circumstances of the loss are known, the loss is against the pledger. There is no deduction made from what is due to the broker at all. Any pledge which perishes in the possession of the broker and the circumstances of its loss are only kn
Grade:

Hadith #1498 - Muwatta Malik (Muwatta Malik)
Yahya said that he heard Malik speak about two men who had a pledge between them. One of them undertook to sell his pledge, and the other one had asked him to wait a year for his due. He said, âIf it is possible to divide the pledge, and the due of the one who asked him to wait will not be decreased, half the pledge which is between them is sold for him and he is given his due. If it is feared that his right will be decreased, all the pledge is sold, and the one who undertook to sell his pledg
Grade:

Hadith #1499 - Muwatta Malik (Muwatta Malik)
Yahya said that he heard Malik speak about someone who pledged goods as security for a loan, and they perished with the broker. The one who took out the loan confirmed its specification. They agreed on the amount of the loan, but challenged each other about the value of the pledge, the pledger saying that it had been worth twenty dinars, whilst the broker said that it had been worth only ten, and that the amount loaned on security was twenty dinars. Malik said, âIt is said to the one in whose
Grade:

Hadith #1500 - Muwatta Malik (Muwatta Malik)
Yahya said that he heard Malik say, âWhat is done in our community about a man who rents an animal for a journey to a specified place and then he goes beyond that place and further, is that the owner of the animal has a choice. If he wants to take extra rent for his animal to cover the distance overstepped, he is given that on top of the first rent and the animal is returned. If the owner of the animal likes to sell the animal from the place where he over-steps, he has the price of the animal
Grade:

Hadith #1501 - Muwatta Malik (Muwatta Malik)
Malik related to me from Ibn Shihab that Abd al-Malik ibn Marwan gave a judgment that the rapist had to pay the raped woman her bride- price. Yahya said that he heard Malik say, âWhat is done in our community about the man who rapes a woman, virgin or non-virgin, if she is free, is that he must pay the bride-price of the like of her. If she is a slave, he must pay what he has diminished of her worth. The hadd-punishment in such cases is applied to the rapist, and there is no punishment applied
Grade:

Hadith #1502 - Muwatta Malik (Muwatta Malik)
Yahya said that he heard Malik say, âWhat is done in our community about someone who consumed an animal without the permission of its owner, is that he must pay its price on the day he consumed it. He is not obliged to replace it with a similar animal nor does he compensate the owner with any kind of animal. He must pay its price on the day it was consumed, and giving the value is more equitable in compensation for animals and goods.â Yahya said that he heard Malik say about someone who cons
Grade:

Hadith #1503 - Muwatta Malik (Muwatta Malik)
Yahya related to me from Malik from Zayd ibn Aslam that the Messenger of Allah, may Allah bless him and grant him peace, said, âIf someone changes his deen â strike his neck!â The meaning of the statement of the Prophet, may Allah bless him and grant him peace, in our opinion and Allah knows best, is that âif someone changes his deen, strike his neck!â refers to those who leave Islam for other than it â like the heretics and their like, about whom it is known. They are killed without
Grade:

Hadith #1504 - Muwatta Malik (Muwatta Malik)
Malik related to me from Abd ar-Rahman ibn Muhammad ibn Abdullah ibn Abd al-Qari that his father said, âA man came to Umar ibn al- Khattab from Abu Musa al-Ashari. Umar asked after various people, and he informed him. Then Umar inquired, âDo you have any recent news?â He said, âYes. A man has become a kafir after his Islam.â Umar asked, âWhat have you done with him?â He said, âWe let him approach and struck off his head.â Umar said, âDidnât you imprison him for three days a
Grade:

Hadith #1505 - Muwatta Malik (Muwatta Malik)
Yahya related to me from Malik from Suhayl ibn Abi Salih as- Samman from his father from Abu Hurayra that Sad ibn Ubada said to the Messenger of Allah, may Allah bless him and grant him peace, âWhat do you think if I find a man with my wife? Shall I grant him a respite until I bring four witnesses?â The Messenger of Allah, may Allah bless him and grant him peace, replied, âYes.â
Grade:

Hadith #1506 - Muwatta Malik (Muwatta Malik)
Malik related to me from Yahya ibn Said from Said ibn al-Musayyab that a Syrian man called Ibn Khaybari found a man with his wife and killed him, or killed them both. Muawiya ibn Abi Sufyan found it difficult to make a decision and he wrote to Abu Musa al-Ashari to ask Ali ibn Abi Talib for him about that. So Abu Musa asked Ali ibn Abi Talib and AIi said to him, âIs this thing in my land? I adjure you, you must tell me.â Abu Musa explained to him how Muawiya ibn Abi Sufyan had written him to
Grade:

Hadith #1507 - Muwatta Malik (Muwatta Malik)
Yahya said that Malik related from Ibn Shihab that Sunayn Abi Jamila, a man from the Banu Sulaym, found an abandoned child in the time of Umar ibn al-Khattab. Sunayn took him to Umar ibn al-Khattab. He asked, âWhat has induced you to take this person?â He answered, âI found him lost, so I took him.â Umarâs advisor said to him,â âAmir al-Muminin! He is a man who does good.â Umar inquired of him, âIs it so?â He replied, âYes.â Umar ibn al-Khattab said, âGo, he is free, an
Grade:

Hadith #1508 - Muwatta Malik (Muwatta Malik)
Yahya said from Malik from Ibn Shihab from Urwa ibn az-Zubayr that Aâisha, the wife of the Prophet, may Allah bless him and grant him peace, said, âUtba ibn Abi Waqqas disclosed to his brother, Sad ibn Abi Waqqas, that he was the father of the son of the slave-girl of Zama, and made him promise to look after him (after his death). In the year of the conquest, Sad took him and said, âHe is the son of my brother. He covenanted with me about him.â Abd ibn Zama stood up and said, âHe is my
Grade:

Hadith #1509 - Muwatta Malik (Muwatta Malik)
Malik related to me from Yazid ibn Abdullah ibn al-Hadi from Muhammad ibn Ibrahim ibn al-Harith at-Taymi from Sulayman ibn Yasar from Abdullah ibn Abi Umayya that a womanâs husband died, and she did the idda of four months and ten days. Then she married when she was free to marry. She stayed with her husband for four and a half months, then gave birth to a fully developed child. Her husband went to Umar ibn al-Khattab and mentioned that to him, so Umar called some of the old women of the Jahil
Grade:

Hadith #1510 - Muwatta Malik (Muwatta Malik)
Malik related to me from Yahya ibn Said from Sulayman ibn Yasar that Umar ibn al-Khattab used to attach the children of the Jahiliyya to whoever claimed them in Islam. Two men came and each of them claimed a womanâs child. Umar ibn al-Khattab summoned a person who scrutinized features and he looked at them. The scrutinizer said, âThey both share in him.â Umar ibn al-Khattab hit him with a whip. Then he summoned the woman, and said, âTell me your tale.â She said, âIt was this one (ind
Grade:

Hadith #1511 - Muwatta Malik (Muwatta Malik)
Malik related to me that he had heard that Umar ibn al-Khattab or Uthman ibn Affan gave a judgement about a slave woman who misled a man about herself and said that she was free. He married her and she bore children. It was decided that he should ransom his children with their like of slaves. Yahya said that he heard Malik say, âTo ransom them with their price is more equitable in this case, Allah willing.â
Grade:

Hadith #1512 - Muwatta Malik (Muwatta Malik)
Yahya said that he heard Malik say, âThe way of doing things generally agreed upon in our community in the case of a man who dies and has sons and one of them claims, âMy father confirmed that so-and- so was his son,â is that the relationship is not established by the testimony of one man, and the confirmation of the one who confirmed it is only permitted as regards his own share in the division of his fatherâs property. The one testified for is only given his due from the share of the t
Grade:

Hadith #1513 - Muwatta Malik (Muwatta Malik)
Yahya said that Malik related from Ibn Shihab from Salim ibn Abdullah ibn Umar from his father that Umar ibn al-Khattab said, âWhatâs the matter with men who have intercourse with their slave- girls and then dismiss them? No slave-girl comes to me whose master confesses that he has had intercourse with her but that I connect her child to him, whether or not he has practised coitus interruptus or stopped having intercourse with her.â
Grade:

Hadith #1514 - Muwatta Malik (Muwatta Malik)
Malik related to me from Nafi that Safiyya bint Abi Ubayd informed him that Umar ibn al-Khattab said, âWhat is the matter with men who have intercourse with their slave-girls and then leave them to go? No slave-girl comes to me whose master confesses that he has had intercourse with her but that I connect her child to him, whether or not he has practised coitus interruptus or left off from intercourse with her.â Yahya said that he heard Malik say, âWhat is done in our community about an um
Grade:

Hadith #1515 - Muwatta Malik (Muwatta Malik)
Yahya related from Malik from Hisham ibn Urwa from his father that the Messenger of Allah, may Allah bless him and grant him peace, said, âIf anyone revives dead land, it belongs to him, and the unjust root has no right.â Malik explained, âThe unjust root is whatever is taken, or planted without right.â
Grade:

Hadith #1516 - Muwatta Malik (Muwatta Malik)
Malik related to me from Ibn Shihab from Salim ibn Abdullah from his father that Umar ibn al-Khattab said, âWhoever revives dead land, it belongs to him.â Malik said, âThat is what is done in our community.â
Grade:

Hadith #1517 - Muwatta Malik (Muwatta Malik)
Yahya related to me from Malik from Abdullah ibn Abi Bakr ibn Muhammad ibn Amr ibn Hazm that he heard that the Messenger of Allah, may Allah bless him and grant him peace, said about the flood-channels of Mahzur and Mudhaynib (in Madina), âDam them systematically, so that the water is diverted into each property in turn up to ankle level, starting upstream.â
Grade:

Hadith #1518 - Muwatta Malik (Muwatta Malik)
Malik related to me from Abuâz-Zinad from al-Araj from Abu Hurayra that the Messenger of Allah, may Allah bless him and grant him peace, said, âExcess water is not withheld in order to prevent herbage from growing.â
Grade:

Hadith #1519 - Muwatta Malik (Muwatta Malik)
Malik related to me from Abuâr-Rijal Muhammad ibn Abd ar-Rahman from his mother Amra bint Abd ar-Rahman that she informed him that the Messenger of Allah, may Allah bless him and grant him peace, said, âDo not withhold the surplus water of a well from people.â
Grade:

Hadith #1520 - Muwatta Malik (Muwatta Malik)
Yahya related to me from Malik from Amr ibn Yahya al-Mazini from his father that the Messenger of Allah, may Allah bless him and grant him peace, said, âThere is no injury nor return of injury.â
Grade:

Hadith #1521 - Muwatta Malik (Muwatta Malik)
Malik related to me from Ibn Shihab from al-Araj from Abu Hurayra that the Messenger of Allah, may Allah bless him and grant him peace, said, âNo one should prevent his neighbour from fixing a wooden peg in his wall.â Then Abu Hurayra said, âWhy do I see you turning away from it? By Allah! I shall keep on at you about it.â
Grade:

Hadith #1522 - Muwatta Malik (Muwatta Malik)
Malik related to me from Amr ibn Yahya al-Mazini from his father that ad-Dahhak ibn Khalifa watered his irrigation ditch from a large source of water. He wanted to have it pass through the land of Muhammad ibn Maslama, and Muhammad refused. Ad-Dahhak said to him, âWhy do you prevent me? It will benefit you. You can drink from it first and last and it will not harm you.â Muhammed refused so ad- Dahhak spoke about it to Umar ibn al-Khattab, and Umar ibn al-Khattab summoned Muhammad ibn Maslama
Grade:

Hadith #1523 - Muwatta Malik (Muwatta Malik)
Malik related to me from Amr ibn Yahya al-Mazini that his father said, âThere was a stream in my grand-fatherâs garden belonging to Abd ar-Rahman ibn Awf Abd ar-Rahman ibn Awf wanted to transfer it to a corner of the garden nearer to his land, and the owner of the garden prevented him. Abd ar-Rahman ibn Awf spoke to Umar ibn al-Khattab about it, and he gave a judgement to Abd ar-Rahman ibn Awf that he should transfer it.â
Grade:

Hadith #1524 - Muwatta Malik (Muwatta Malik)
Yahya related to me from Malik that Thawr ibn Zayd ad-Dili said, âI heard that the Messenger of Allah, may Allah bless him and grant him peace, said, âA house or land that has been divided in the Jahiliyya, it is according to the division of the Jahiliyya. A house or land which has not been divided before the coming of Islam is divided according to Islam.â â
Grade:

Hadith #1525 - Muwatta Malik (Muwatta Malik)
Yahya said that he heard Malik speak about a man who died and left properties in Aliya and Safila (outlying districts of Madina). He said, âUnirrigated naturally watered land is not in the same category as irrigated land unless the family are satisfied with that. Unirrigated land is only in the same category as land with a spring when it resembles it. When the properties are in one land, and are close together, each individual property is evaluated and then divided between the heirs. Dwellings
Grade:

Hadith #1526 - Muwatta Malik (Muwatta Malik)
Yahya related to me from Malik from Ibn Shihab from Haram ibn Sad ibn Muhayyisa that a female camel of al-Bara ibn Azib entered the garden of a man and it did some damage to it. The Messenger of Allah, may Allah bless him and grant him peace, gave a judgement that the people of the garden were responsible for guarding it in the day, and the owner of the animals was liable for what the animals destroyed at night.
Grade:

Hadith #1527 - Muwatta Malik (Muwatta Malik)
Malik related to me from Hisham ibn Urwa from his father from Yahya ibn Abd ar-Rahman ibn Hatib that some slaves of Hatib stole a she-camel belonging to a man from the Muzayna tribe and they slaughtered it. The case was brought before Umar ibn al-Khattab, and Umar ordered Kathir ibn as-Salt to cut off their hands. Then Umar said to Habib, âI think you must be starving them,â and he added, âBy Allah! I will make you pay such a fine that it will be heavy for you.â He enquired of the man fr
Grade:

Hadith #1528 - Muwatta Malik (Muwatta Malik)
Yahya said that he heard Malik say, âWhat is done in our community about injury to a domestic animal, is that the one who injures it must pay the amount by which he has diminished the animalâs price.â Yahya said that he heard Malik speak about a camel who attacked a man and he feared for himself and killed it or hamstrung it. He said, âIf he has a clear proof that it was heading for him and had attacked him, there are no damages against him. If there is no clear proof except his word, he
Grade:

Hadith #1529 - Muwatta Malik (Muwatta Malik)
Yahya related that he heard Malik say that if a man gave a washer a garment to dye and he dyed it, and then the owner of the garment said, âI did not order you to use this dye,â and the washer protested that he had done so, then the washer was to be believed. It was the same with the tailor and the gold-smith. They took an oath about it unless they produced something they would not normally have been employed to do. In that situation their statement was not allowed and the owner of the garme
Grade:

Hadith #1530 - Muwatta Malik (Muwatta Malik)
Yahya said that he heard Malik say, âWhat is done in our community about a man who refers a creditor to another man for the debt he owes him is that if the one referred to goes bankrupt or dies, and does not leave enough to pay the debt, then the creditor has nothing against the one who referred him and the debt does not return to the first party.â Malik said, âThis is the way of doing things about which there is no dispute in our community.â Malik said, âIf a man has his debt to someb
Grade:

Hadith #1531 - Muwatta Malik (Muwatta Malik)
Yahya said that he heard Malik say, âIf a man buys a garment which has a defect, a burn or something else, which the seller knows about and that is testified against him or he confirms it, and the man who has bought it causes a new tear which decreases the price of the garment, and then he learns about the original defect, he can return it to the seller and he is not liable for his tearing it. âIf a man buys a garment which has a defect of a burn or flaw, and the one who sold it to him claim
Grade:

Hadith #1532 - Muwatta Malik (Muwatta Malik)
Yahya related to us from Malik from Ibn Shihab from Humayd ibn Abd ar-Rah man ibn Awf and from Muhammad ibn an-Numan ibn Bashir that they related to him that an-Numan ibn Bashir said that his father Bashir brought him to the Messenger of Allah, may Allah bless him and grant him peace, and said, âI have given this son of mine one of my slaves.â The Messenger of Allah, may Allah bless him and grant him peace, said, âHave you given each of your children the same as this?â He said, âNo.â
Grade:

Hadith #1533 - Muwatta Malik (Muwatta Malik)
Malik related to me from Ibn Shihab from Urwa ibn az-Zubayr that Aâisha, the wife of the Prophet, may Allah bless him and grant him peace, said, âAbu Bakr as-Siddiq gave me palm trees whose produce was twenty awsuq from his property at al-Ghaba. When he was dying, he said, âBy Allah, little daughter, there is no one I would prefer to be wealthy after I die than you. There is no one it is more difficult for me to see poor after I die than you. I gave you palm-trees whose produce is twenty a
Grade:

Hadith #1534 - Muwatta Malik (Muwatta Malik)
Malik related to me from Ibn Shihab from Urwa ibn az-Zubayr from Abd ar-Rahman ibn Abd al-Qari that Umar ibn al-Khattab said, âWhat is wrong with men who give their sons gifts and then keep them and if the son dies, they say, âMy property is in my possession and I did not give it to anyone.â But if they themselves are dying, they say, âIt belongs to my son, I gave it to him.â Whoever gives a gift, and does not hand it over to the one to whom it was given, the gift is invalid, and if he
Grade:

Hadith #1535 - Muwatta Malik (Muwatta Malik)
Yahya said that he heard Malik say, âWhat is done in our community about some one who gives a gift not intending a reward is that he calls witnesses to it. It is affirmed for the one to whom it has been given unless the giver dies before the one to whom it was given receives the gift.â He said, âIf the giver wants to keep the gift after he has had it witnessed, he cannot. If the recipient claims it from him, he takes it.â Malik said, âIf some one gives a gift and then withdraws it and
Grade:

Hadith #1536 - Muwatta Malik (Muwatta Malik)
Malik related to me from Daâud ibn al-Husayn from Abu Ghatafan ibn Tarif al-Muriyi that Umar ibn al-Khattab said, âIf someone gives a gift to strengthen ties with a relative or as sadaqa, he cannot have it returned. If some one, however, gives a gift seeking by it favour or reward, he has his gift and can reclaim it if he does not have satisfaction from it.â Yahya said that he heard Malik say, âThe generally agreed-on way of doing things in our community is that if the gift is returned t
Grade:

Hadith #1537 - Muwatta Malik (Muwatta Malik)
Yahya said that he heard Malik say, âThe way of doing things in our community about which there is no dispute, is that if a man gives sadaqa to his son â sadaqa which the son takes possession of or which is in the fatherâs keeping and the father has had his sadaqa witnessed, he cannot take back any of it because he cannot reclaim any sadaqa.â Yahya said that he heard Malik say, âThe generally agreed-on way of doing things in our community in the case of someone who gives his son a gift
Grade:

Hadith #1538 - Muwatta Malik (Muwatta Malik)
Malik related to me from Ibn Shihab from Abu Salama ibn Abd ar- Rahman ibn Awf from Jabir ibn Abdullah al-Ansari that the Messenger of Allah, may Allah bless him and grant him peace, said, âIf someone is given a life pension, for him and his posterity, it belongs to the person to whom it has been given. It never reverts to the one who gave it because he gave a gift and the rules of inheritance apply to it.â
Grade:

Hadith #1539 - Muwatta Malik (Muwatta Malik)
Malik related to me from Yahya ibn Said that Abd ar-Rahman ibn al-Qasim ibn Muhammad heard Makhul ad-Dimashqi ask al-Qasim ibn Muhammad about the life pension and what people said about it. Al- Qasim ibn Muhammad said, âI have only come upon people who keep to the conditions they make about their property and what they are given.â Yahya said that he heard Malik say, âWhat is done in our community is that the life pension reverts to the one who makes it a life pension unless he says, âIt
Grade:

Hadith #1540 - Muwatta Malik (Muwatta Malik)
Malik related to me from Nafi that Abdullah ibn Umar inherited the house of Hafsa bint Umar. He said, âHafsa gave lodging to the daughter of Zayd ibn al-Khattab for as long as she lived. When the daughter of Zayd died, Abdullah ibn Umar took possession of the dwelling and considered that it was his.â
Grade:

Hadith #1541 - Muwatta Malik (Muwatta Malik)
Malik related to me from Rabia ibn Abi Abd ar-Rahman from Yazid, the mawla of al-Munbaith that Zayd ibn Khalid al-Juhani said, âA man came to the Messenger of Allah, may Allah bless him and grant him peace, and asked him about finds. He said, âMemorize the characteristics of the object found, then publicise it for a year. If the owner comes, give it to him. If not, then it is your business.â He said, âWhat about lost sheep, Messenger of Allah?â He said, âThey are yours, your brotherâ
Grade:

Hadith #1542 - Muwatta Malik (Muwatta Malik)
Malik related to me from Ayyub ibn Musa from Muawiya ibn Abdullah ibn Badr al-Juhani that his father informed him that he stopped with a people on the way to Syria and he found a purse which had eighty dinars in it. He mentioned that to Umar ibn al-Khattab. Umar said to him, âAnnounce it at the doors of the mosques and mention it to everyone who comes from Syria for a year. When a year passes, it is your business.â
Grade:

Hadith #1543 - Muwatta Malik (Muwatta Malik)
Malik related to me from Nafi that a man found something and went to Abdullah ibn Umar and said to him, âI have found something. What do you think I should do about it?â Abdullah ibn Umar said to him, âPublicise it!â He said, âI have done so.â He said, âDo it again.â He said, âI have done so.â Abdullah said, âI do not order you to use it. If you wished, you could have left it.â
Grade:

Hadith #1544 - Muwatta Malik (Muwatta Malik)
Yahya said that he heard Malik say, âWhat is done in our community about a slave who finds something and uses it before the term which is set for finds has been reached, and that is a year, is that it is against his person. Either his master gives the price of what his slave has used, or he surrenders his slave to them as compensation. If he withheld it until the term was reached which is set for finds and he used it, it is a debt against him which follows him and it is not against his person
Grade:

Hadith #1545 - Muwatta Malik (Muwatta Malik)
Malik related to me from Yahya ibn Said from Sulayman ibn Yasar that Thabit ibn ad-Dahhak al-Ansari told him that he had found a camel at Harra, so he hobbled it and mentioned it to Umar ibn al-Khattab and Umar ordered him to make it known three times. Thabit said to him, âThat would distract me from the running of my estate.â Umar said to him, âThen let it go where you found it.â
Grade:

Hadith #1546 - Muwatta Malik (Muwatta Malik)
Malik related to me from Yahya ibn Said from Said ibn al-Musayyab that Umar ibn al-Khattab said while he was leaning his back against the Kaba, âWhoever takes a stray is astray.â
Grade:

Hadith #1547 - Muwatta Malik (Muwatta Malik)
Malik related to me that he heard Ibn Shihab say, âThe stray camels in the time of Umar ibn al-Khattab were numerous and left alone. No one touched them until the time of Uthman ibn Affan. He ordered that they be publicised and then sold, and if the owner came afterwards, he was given their price.â
Grade:

Hadith #1548 - Muwatta Malik (Muwatta Malik)
Malik related to me from Said ibn Amr Shurahbil ibn Said ibn Sad ibn Ubada from his father that his father said, âSad ibn Ubada went out with the Messenger of Allah, may Allah bless him and grant him peace, in one of his raids and his mother was dying in Madina. Someone said to her, âLeave a testament.â She said, âIn what shall I leave a testament? The property is Sadâs property.â Then she died before Sad returned. When Sad ibn Ubada returned, that was mentioned to him. Sad said, â
Grade:

Hadith #1549 - Muwatta Malik (Muwatta Malik)
Malik related to me from Hisham ibn Urwa from his father from Aâisha, the wife of the Prophet, may Allah bless him and grant him peace, that a man said to the Messenger of Allah, may Allah bless him and grant him peace, âMy mother died suddenly, and I think that had she spoken, she would have given sadaqa. Shall I give sadaqa for her?â The Messenger of Allah, may Allah bless him and grant him peace, said, âYes.â
Grade:

Hadith #1550 - Muwatta Malik (Muwatta Malik)
Malik related to me that he heard that a man of the Ansar from the tribe of Banu al-Harith ibn al-Khazraj, gave sadaqa to his parents and then they died. Their son inherited the property he had given them and it was palm-trees. He asked the Messenger of Allah, may Allah bless him and grant him peace, about it and he said, âYou are rewarded for your sadaqa, and take it as your inheritance.â
Grade: